The Impact of Deposit Materials on Environment Pollution Around Industrial Areas in Kosovo - DEMAKU, Skender; ZUZAKU, Islam; SYLEJMANI, Donika; ALIU, Arbnora (Research Advances in Environment, Geography and Earth Science Vol. 10, 2024)
Human evolution, together with the industrial revolution, has caused great changes in the quality of the natural environments, in which man lives and exercises his activity. The soil plays an important role in this process, as it serves as a “repository” for the accumulation of chemical pollutants. Heavy metals, unlike organic pollutants, are not biodegradable. The presence of these pollutants in the environment is related to industrial activities, emissions during the burning of fossil materials, family economy and traffic. Also, persistent organic pollutants (POPs) remain at the center of scientific attention, due to their low degradation rate, lipophilic nature, toxicity, ability to be transported over long distances, and to bioaccumulate in living organisms. Around 70 years ago, various manufacturing industries were established in Kosovo, primarily focusing on ferrous metallurgy and coal extraction for electricity production. Many of these manufacturing industries are still operational today, though some no longer function at their full production capacity as they did two decades ago.